Effectiveness of Ozone Plasma Technology in Enhancing the Survival of Gourami (Osphronemus goramy) Fish Eggs - Zahar, Intan; Sari, Dian Puspita; Hasanah, Moraida; Z, Fynnisa (Talenta Publisher, 2025)
The gourami (Osphronemus goramy) fish is a freshwater fish commonly found in Asia and widely cultivated by fish farmers or local inhabitants. The survival rate of gourami fish from egg to larva and juvenile stages is very low, at approximately 50%. Several factors, such as unstable environmental conditions, poor water quality, and fungal growth on the eggs, cause this. Typically, synthetic medications or natural materials such as betel leaves and others are used to improve gourami fry's survival rate. In this study, the researchers attempted to apply ozone plasma technology dissolved in water to observe the egg hatchability of gourami fish. This study aims to apply technology in fisheries and aquatic sciences. The results of the study show that ozone technology can be applied to observe larval survival, with the highest survival rates found in the 10-minute and 15-minute ozone treatments, both achieving 100% hatchability, with larval survival rates of 86.67% and 96.66%, respectively.